2019
DOI: 10.1158/1055-9965.epi-19-0165
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the World Cancer Research Fund/American Institute for Cancer Research 2018 Recommendations for Cancer Prevention and Risk of Colorectal Cancer

Abstract: Background: The World Cancer Research Fund/American Institute for Cancer Research (WCRF/AICR) 2018 diet, nutrition, and physical activity recommendations aim to reduce cancer risk. We examined adherence to the WCRF/AICR recommendations and colorectal cancer risk in two prospective cohorts.Methods: We followed 68,977 women in the Nurses' Health Study and 45,442 men in the Health Professionals Follow-up Study from 1986 until 2012. We created cumulatively averaged WCRF/AICR scores using updated diet, adiposity, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 67 publications
3
50
0
Order By: Relevance
“…We found similar results when using scores measuring overall adherence to the 2007 and 2018 guidelines, and our findings are largely in agreement with previous studies relying on recommendations from the earlier WCRF/AICR report. Along this line, recent findings on the association between the 2018 WCRF/AICR recommendation and colorectal cancer risk from the Nurses' Health Study and Health Professionals Follow-up Study confirmed the results of prior studies based on the 2007 guidelines release [47].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…We found similar results when using scores measuring overall adherence to the 2007 and 2018 guidelines, and our findings are largely in agreement with previous studies relying on recommendations from the earlier WCRF/AICR report. Along this line, recent findings on the association between the 2018 WCRF/AICR recommendation and colorectal cancer risk from the Nurses' Health Study and Health Professionals Follow-up Study confirmed the results of prior studies based on the 2007 guidelines release [47].…”
Section: Discussionsupporting
confidence: 79%
“…Only a few reports investigated the association between the 2018 release of the WCRF/AICR recommendations and cancer risk [42,[46][47][48]. The present study is the first evaluating the updated recommendations in the prevention of invasive breast cancer.…”
Section: Discussionmentioning
confidence: 92%
“…In agreement with the results obtained, El Kinany and coworkers [16] found that greater adherence to the 2018 WCRF/AICR score decreased overall CRC risk by 42% after comparing 1516 cases with 1516 controls in Morocco. Similarly, a 24-year-follow-up cohort study [13], with 68,977 women from the Nurses' Health Study and 45,442 men from the Health Professionals Follow-up Study, found a statistically significant inverse association between adherence to the updated WCRF/AICR score and the incidence of CRC risk in men. Furthermore, associations in women were weaker.…”
Section: Discussionmentioning
confidence: 89%
“…Some prospective cohort studies [6,[8][9][10][11][12][13] and case-control studies [14][15][16] have evaluated the associations between CRC risk and adherence to cancer-specific nutritional recommendations with inconsistent results. However, limited longitudinal studies [13,16] have been conducted to assess associations based on the updated 2018 WCRF/AICR recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…With the ongoing societal and economic development, the incidence of CRC is becoming more and higher, especially in Asia countries with low incidence. In recent years, the incidence rate is close to the level of European and American countries [3,4].…”
Section: Introductionmentioning
confidence: 88%